2017
DOI: 10.1016/j.ihj.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The role of acute circulatory support in ST-segment elevation myocardial infarction complicated by cardiogenic shock

Abstract: In the setting of ST-segment elevation myocardial infarction (STEMI) complicated by cardiogenic shock, three primary treatment objectives include providing circulatory support, ventricular unloading, and restoring myocardial perfusion. In addition to primary percutaneous coronary intervention, each of these three objectives can be achieved with appropriate use of an acute mechanical circulatory support (AMCS) pump. Over the past decade, utilization of percutaneously-delivered AMCS devices including the Impella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…It reduces afterload, increases stroke volume, optimizes coronary flow, and decreases oxygen consumption 27 (Figure 2A). 28,29 However, a meta-analysis reported no differences in short-term or long-term mortality in CS patients supported with IABP. 30 TandemHeart is a percutaneous continuous-flow centrifugal pump providing circulatory support of up to 5 L/min, but it requires trans-septal puncture, as it is inserted into the femoral vein and advanced across the interatrial septum into the left atrium.…”
Section: Temporary Mcs In Csmentioning
confidence: 99%
See 4 more Smart Citations
“…It reduces afterload, increases stroke volume, optimizes coronary flow, and decreases oxygen consumption 27 (Figure 2A). 28,29 However, a meta-analysis reported no differences in short-term or long-term mortality in CS patients supported with IABP. 30 TandemHeart is a percutaneous continuous-flow centrifugal pump providing circulatory support of up to 5 L/min, but it requires trans-septal puncture, as it is inserted into the femoral vein and advanced across the interatrial septum into the left atrium.…”
Section: Temporary Mcs In Csmentioning
confidence: 99%
“…7,31 This device unloads the left atrium, ultimately decreasing LV end-diastolic volumes. 16,29 Thiele et al looked at patients who were randomized to IABP or TandemHeart and found greater improvements in cardiac power, cardiac index, pulmonary arterial pressure, and pulmonary capillary wedge pressure but had similar 30-day mortality (43% vs 45%, P = .86). 32 Another study retrospectively looked at patients referred for TandemHeart and found that survival was significantly influenced by implant indication with 23.8% surviving in bridge to recovery versus 51% in bridge to left ventricular assist device (LVAD) or surgery ( P = .04).…”
Section: Temporary Mcs In Csmentioning
confidence: 99%
See 3 more Smart Citations